Performance and Projected Impact of Synovial Fluid Polymerase Chain Reaction Testing for Patients Evaluated for Septic Arthritis - Mark T Steele; Amy M Stubbs; Anusha Krishnadasan; Laurie Kemble; Ruoyu Li; William R Mower; Joseph Liao; Gregory J Moran; David A Talan; Danielle Beckham; Kavitha Pathmarajah; Jon Femling; et al. (Clinical Infectious Diseases, 2026)
Abstract Background Septic arthritis is an infectious disease emergency. Diagnosis is limited by low sensitivity of synovial fluid cell count and Gram stain and delayed culture results. The impact of PCR testing on clinical care of patients suspected of septic arthritis is unknown. Methods We conducted a prospective, observational study (2021-23) at nine US EDs of adults evaluated for septic arthritis with synovial fluid culture, and later PCR-tested residual fluid. We report PCR concordance, sensitivity and specificity compared to culture, 30-day diagnosis, and antibiotic delay >1 day, and project the impact of point-of-care PCR resulting. Results Of 475 participants, 126 (26.5%) were diagnosed with septic arthritis. Eighty-eight (18.5%) had positive PCR and 80 (16.8%) had positive culture identifying, respectively, Staphylococcus aureus (36 [40.9%] vs. 29 [36.3%]), streptococci (32 [36.4%] vs. 22 [27.5%]), and Neisseria gonorrhoeae (12 [13.6%] vs. 4 [5.0%]). PCR-culture concordance was 89.5%. For PCR-targeted organisms, PCR sensitivity and specificity were 89.2% (95%CI 79.4%-94.7%) and 95.3% (95%CI 92.5%-97.1%), respectively. Fifty-seven (45.2%) participants with septic arthritis had concordant-positive PCR/culture results; 11 (19.3%) had delayed treatment (1-6 days). Nineteen (15.1%) participants with septic arthritis had a PCR-positive/culture-negative result, which occurred more frequently with antibiotic pre-treatment and N. gonorrhoeae; all were treated empirically. Among 28 (5.9%) participants with PCR-positive/culture-negative results, 24 (85.7%) were diagnosed with septic arthritis, endocarditis/bacteremia, or osteomyelitis. Three participants with only PCR-detected N. gonorrhoeae did not receive treatment for this infection. Conclusions Adjunctive point-of-care PCR testing would be projected to increase timeliness of ED septic arthritis diagnosis and pathogen-specific treatment. Trial registration ClinicalTrials.gov Identifier: NCT05341908